If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1y + z = -11 Solving 2x + -1y + z = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 2x + -1y + y + z = -11 + y Combine like terms: -1y + y = 0 2x + 0 + z = -11 + y 2x + z = -11 + y Add '-1z' to each side of the equation. 2x + z + -1z = -11 + y + -1z Combine like terms: z + -1z = 0 2x + 0 = -11 + y + -1z 2x = -11 + y + -1z Divide each side by '2'. x = -5.5 + 0.5y + -0.5z Simplifying x = -5.5 + 0.5y + -0.5z
| -1+2x=28+13 | | t/6-2=11 | | kx-3=5 | | u/7=17.92 | | P=344x-560 | | 8v=20.40 | | 3n+8+12n-5-7n+11= | | X-11/2=9 | | 7x=2/3 | | 8/1=.22/n | | 1/7(-21x-2) | | 3x+88=14x | | 6q-4=2q-12 | | 56=9w-w | | 20k-11=9k-99 | | 1-2x^2/sinx | | x/4-4=3 | | 180-120.4= | | 6x-1=16-51 | | 8r+15=95 | | a+bi=-9i+4i | | 7(23.2)-42= | | a+bi=9i+4i | | ((2/3x)^1/3)-((10/3x)^-2/3)=0 | | 25(r-2)=320(r-4) | | z^2-(4-6i)z-4-12i=0 | | 3x-4iy=-9y+i(5+x) | | 4q-2q=4-12 | | fx=(7-3x)(3x+7) | | 3x-87=18 | | x^2-14=9 | | 2+3s=8 |